Indocyanine green nebulization visualizes the pulmonary bronchus during video-assisted thoracoscopic surgery - Hao Xu; Xun Wu; Songjing Zhao; Zhenfan Wang; Guanchao Jiang; Yun Li; Jian Zhou (Journal of Cardiothoracic Surgery)
Abstract Background Intraoperative tracheobronchial injury is a rare but serious complication of lung surgery. With the increasing number of segmentectomies, surgeons need to locate finer and less easily identified segmental bronchi or even subsegmental bronchi. However, there is no simple or feasible method for visualizing the bronchus during surgery. Case presentation Herein, we report a case in which indocyanine green (ICG) inhalation was used to visualize the pulmonary bronchus during video-assisted thoracoscopic surgery. The patient was a woman with a GGO located in the anterior segment of the right upper lobe, and thoracoscopic segmentectomy was scheduled. ICG (3.75 mg/ml) was inhaled into the lung on the operative side after single-lung ventilation for 5 min. During surgery, the anterior segmental bronchus was difficult to locate accurately. Under the overlay imaging window of the NIF imaging system, the bronchus was shown in green, indicating the bronchi in contrast to the surrounding lung tissue. We dissected the bronchi with the assistance of fluorescence imaging and were surprised to find that the bifurcation of the anterior and apical bronchi could be clearly identified by navigation via the inhaled ICG and NIF system. Segmentectomy was successfully performed, and no adverse events were recorded. Conclusion This case showed that ICG nebulization is feasible and safe for visualizing the pulmonary bronchus during thoracoscopic surgery. This method has great application potential for reducing intraoperative tracheobronchial injury.